Do ‘leaders’ in change sound different from ‘laggers’? The perceptual similarity of New Zealand English voices - Elena Sheard; Jen Hay; Joshua Wilson Black; Lynn Clark (PLoS ONE, 2025)
Work on covariation in New Zealand English has revealed groups of speakers characterised by their back vowel spaces and status as ‘leaders’ or ‘laggers’ across a set of ongoing vowel changes. We investigate whether listeners hear speakers from different groups as perceptually distinct. We conduct a perception task in which New Zealanders rate the similarity of pairs of speakers. We use the results to create a two-dimensional perceptual similarity space by means of Multi-Dimensional Scaling, and test if speakers are organised within this space according to their back vowels, leader-lagger status, speed, or mean pitch. Results indicate higher pitched and faster speakers are perceptually distinct from lower pitched and slower speakers. Leaders are perceptually distinct from laggers if they are not markedly higher pitched. A Generalised Additive Mixed Model fit to the trial-by-trial ratings shows order effects, revealing that perception of similarity is not symmetrical. They also support the perceptual relevance of speaker speed, pitch and leader-lagger status.